Unusual Neisseria species as a cause of infection in patients taking eculizumab. Issue 2 (February 2019) - Crew, Page E.; McNamara, Lucy; Waldron, Peter E.; McCulley, Lynda; Jones, S. Christopher; Bersoff-Matcha, Susan J.
Highlights: Eculizumab is a monoclonal antibody and a terminal complement inhibitor. Eculizumab is known to increase risk for meningococcal disease. We report 7 cases of unusual Neisseria spp. infection in eculizumab recipients. Any Neisseria spp. may cause invasive infectious disease in eculizumab recipients. Summary: Background: Non-meningococcal, non-gonococcal Neisseria spp. are typically commensal and rarely cause invasive disease. Eculizumab is a terminal complement inhibitor that increases susceptibility to meningococcal disease, but data on disease caused by typically-commensal Neisseria spp. are lacking. This series describes postmarketing reports of typically-commensal Neisseria spp. disease in patients receiving eculizumab. Methods: We searched the FDA Adverse Event Reporting System (FAERS) and medical literature for reports of commensal Neisseria spp. disease in patients receiving eculizumab, from eculizumab U.S. approval (2007) through January 31, 2018. Results: We identified seven FAERS reports (including one case also reported in the literature) of non-meningococcal, non-gonococcal Neisseria disease, including N. sicca (mucosa)/subflava ( n  = 2), N. cinerea ( n  = 2), N. sicca (mucosa) ( n  = 1), N. mucosa ( n  = 1, with concurrent alpha-hemolytic Streptococcus bacteremia), and N. flavescens (subflava) ( n  = 1) . Four cases had sources of patient immunosuppression in addition to eculizumab. Three patients had sepsis ( n  = 2) or septic shock ( n  = 1). Five patients were bacteremic. All patients were hospitalized; the infections resolved with antibiotics. Conclusions: Our search identified seven cases of disease from typically commensal Neisseria spp. in eculizumab recipients. These findings suggest that any Neisseria spp. identified from a normally sterile site in an eculizumab recipient could represent true infection warranting prompt treatment.